2016
DOI: 10.1245/s10434-016-5650-0
|View full text |Cite
|
Sign up to set email alerts
|

Robotically Assisted Laparoscopic Ovarian Transposition in Women with Lower Gastrointestinal Cancer Undergoing Pelvic Radiotherapy

Abstract: Background Pelvic radiotherapy (RT) is a standard component of the management for patients with locally advanced rectal cancer or squamous cell carcinoma of the anus. Pelvic RT leads to permanent and irreversible ovarian failure in young women. This study aimed to determine the effectiveness of robotically assisted laparoscopic ovarian transposition (OT) before RT in women with rectal or anal cancer who wanted to preserve normal ovarian function. Methods The study reviewed the medical records of all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Reproductive and oncologic outcomes of robotically assisted laparoscopic ovarian transposition have proven this modality is safe. A recent study found that the use of robotically assisted laparoscopic ovarian transposition leads to preservation of ovarian function in two-thirds of patients with lower gastrointestinal cancer undergoing pelvic radiotherapy [72]. To prevent ovarian remigration, it is recommended that oophoropexy be timed to coincide with treatment.…”
Section: Established Fertility Preservation Methods For Femalesmentioning
confidence: 99%
“…Reproductive and oncologic outcomes of robotically assisted laparoscopic ovarian transposition have proven this modality is safe. A recent study found that the use of robotically assisted laparoscopic ovarian transposition leads to preservation of ovarian function in two-thirds of patients with lower gastrointestinal cancer undergoing pelvic radiotherapy [72]. To prevent ovarian remigration, it is recommended that oophoropexy be timed to coincide with treatment.…”
Section: Established Fertility Preservation Methods For Femalesmentioning
confidence: 99%
“…According to the Ferti PROTEKT guidelines, chemotherapy (QT) regimens for colorectal cancer treatment are considered to be low to medium risk in terms of fertility failure . However, pelvic radiation with a cumulative dose of 50 Gy – usually administered for rectal cancer – has been reported to induce premature failure of ovarian function in more than 90% of patients . Laparoscopic OT has previously been described in the literature as a suitable surgical approach for preserving ovarian hormonal function .…”
mentioning
confidence: 99%
“…Fertility preservation can be also achieved by combination with additional procedures (e.g. ovarian cortex biopsy and vitrification) . Therefore, OT should be considered in women under 40 years of age with adequate ovarian follicle reserve (defined as anti‐Müllerian hormone levels > 1.0 ng/ml and follicle‐stimulating hormone levels < 10 mIU/ml) who have a very low risk of ovarian micro‐metastasis and are receiving chemotherapy with low gonadotoxic effects (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations